Fabrication of the polyetherketoneketone-reinforced nano-hydroxyapatite composites as inspired by the cortical bone - Zhongyi Wang; Yadong Zhang; Junyi Zhao; Chenyang Xie; Qiang Wei; Haiyang Yu (Supramolecular Materials)
Cortical bone has superior mechanical performance. Hydroxyapatite (HA) as its main component are attractive bioactive materials, but possess weak strength. The critical factor is the difference in the structure. Inspired by the hierarchical and delicate architecture of the cortical bone, we used a slurry with 2 wt% polyvinyl alcohol (PVA) and 20 vol% polydopamine-modified nano HA (nHA, pDA-nHA) to fabricate stronger scaffolds characterized by a lamellar structure. Additionally, we immersed the pDA-nHA scaffolds into the polyetherketoneketone (PEKK) synthesis system to reinforce the scaffolds. The cortical bone-inspired composites were produced successfully, and the 20 vol% pDA-nHA+2 wt% PVA/PEKK composites had the highest strength and modulus. It provides a new solution for enhancing the mechanical strength of the single component, as well as improving the bioactivity of PEKK.